Confronting a Trinity of Institutional Barriers: Denial, Cover‐Up, and Secrecy. Issue 3 (November 2015) - Barker, Holly M.
Abstract: Discourses of government and the nuclear industry erase previous fear and knowledge about the damages and injuries from nuclear weapons that impact indigenous communities. This cover‐up enables nuclear states and nuclear industries to promote nuclear energy as a viable response to climate change. Many people, including environmentalists, consider nuclear energy to be the only viable energy source for the future global economy in that it does not contribute to climate change. It is difficult for us to consider the full scope of the risks that accompany decisions to embrace nuclear energy as a means to reduce greenhouse gas emissions, however, because lessons learned about radiation remain secret or silenced.